Ambient fine particulate matter induces inflammatory responses of vascular endothelial cells through activating TLR-mediated pathway. (October 2019) - Le, Yifei; Hu, Xiao; Zhu, Ji; Wang, Cui; Yang, Zhen; Lu, Dezhao
This study aims to investigate the role of Toll-like receptors (TLRs) on fine particulate matter (PM2.5 )-induced inflammatory responses of vascular endothelial cells. Inflammatory factors and TLRs were examined in the aorta of mice after nonsurgical intratracheal instillation of PM2.5 as well as in the human umbilical vein endothelial cells (HUVECs) treated with PM2.5 . In addition, the effects of TLR2 and TLR4 inhibitors in the secretion of interleukin 6 (IL-6) and IL-1β and the expression of TLRs were determined in the HUVECs. The results showed that PM2.5 could increase the expression of IL-1β, IL-6, TLR2, and TLR4 in vitro and in vivo . Anti-TLR2 IgG or TAK242, an inhibitor of TLR4, decreased the secretion of IL-1β and IL-6 by HUVECs and reduced the expression of corresponding TLRs. In conclusion, we demonstrate that both TLR2 and TLR4 are involved in PM2.5 -induced inflammatory responses of vascular endothelial cells. Inhibition of TLR2 and TLR4 expression has the potential to prevent PM2.5 -induced cardiovascular diseases.